The Feasibility of a Land Ferry System to Reduce Highway Maintenance Cost and Associated Externalities. (23rd June 2016) - Merrill, Steve J.; Paz, Alexander; Molano, Victor; Shrestha, Pramen P.; Maheshwari, Pankaj; Stephen, Haroon; de la Fuente-Mella, Hanns
Abstract : This study provides an economic evaluation for a Land Ferry, which is a rail system capable of carrying trucks and all other types of vehicles, passengers, and cargo. The Land Ferry system involves a sliding loading system to roll heavy loads onto a flatbed; as a result, loading and unloading of all vehicles and cargo could be accomplished simultaneously. The evaluation for this system included (1) the design of a new track alignment over which the Land Ferry system would run, (2) evaluation of various sources of power, (3) estimation of how many local jobs the Land Ferry would generate, and (4) a benefit-cost analysis. It was estimated that the Land Ferry would create over 45, 788 temporary jobs in Nevada during the three-year construction period and 318 permanent jobs during operation. The majority of the benefits were attributed to savings in travel time (356.4 M), vehicle operating costs (1000.4 M), reduction of accidents (544.6 M), and pavement maintenance (503.2 M). These benefits would be a consequence of the shift of trucks from the highway, thus resulting in higher speeds, decrease fuel consumption, and decrease vehicle maintenance costs. The overall benefit-cost ratio of 1.7 implies a cost-effective project.